2016
DOI: 10.3847/0004-637x/825/1/7
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Normal Galaxy X-Ray Emission Through Cosmic History: Constraints From the 6 MS Chandra Deep Field-South

Abstract: We present measurements of the evolution of normal-galaxy X-ray emission from z ≈ 0-7 using local galaxies and galaxy samples in the ≈6 Ms Chandra Deep Field-South (CDF-S) survey. The majority of the CDF-S galaxies are observed at rest-frame energies above 2 keV, where the emission is expected to be dominated by X-ray binary (XRB) populations; however, hot gas is expected to provide small contributions to the observedframe < ∼ 1 keV emission at z < ∼ 1. We show that a single scaling relation between X-ray lumi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
289
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(333 citation statements)
references
References 121 publications
34
289
2
1
Order By: Relevance
“…M12 apply corrections based on locally-calibrated scaling relations (Ranalli et al 2003), whereas we apply a larger correction based on our work in Paper I that indicates a larger X-ray luminosity per unit SFR at these redshifts (see also Lehmer et al 2016). Our measurements still reveal a clear "AGN main sequence" at z ∼ 2, although there are indications that the slope may be steeper than unity due to a suppression of AGN activity at lower stellar masses.…”
Section: Average Agn Accretion Rates and The Agn Main Sequencementioning
confidence: 93%
“…M12 apply corrections based on locally-calibrated scaling relations (Ranalli et al 2003), whereas we apply a larger correction based on our work in Paper I that indicates a larger X-ray luminosity per unit SFR at these redshifts (see also Lehmer et al 2016). Our measurements still reveal a clear "AGN main sequence" at z ∼ 2, although there are indications that the slope may be steeper than unity due to a suppression of AGN activity at lower stellar masses.…”
Section: Average Agn Accretion Rates and The Agn Main Sequencementioning
confidence: 93%
“…where α, β, γ and δ are parameters for which we adopt the values measured by Lehmer et al (2016) in both the soft and hard band, and include the intrinsic scatter in the relation. For the underlying galaxy population we use a semi-analytic galaxy formation model based on the Millennium simulation (Henriques et al 2015), which is in good agreement with the observed star formation history and stellar mass function as a function of redshift.…”
Section: Discussionmentioning
confidence: 99%
“…Using more conservative criteria, such as requiring that the 1 The integrated X-ray emission from high-mass and low-mass XRB in a galaxy can reach luminosities of logL X ≈ 42 (i.e. Lehmer et al 2016). At z > 3, the flux limit of the 7 Ms CDF-S corresponds to logL X 42.…”
Section: Agn Parent Sample and Redshifts In The 7 Ms Cdf-smentioning
confidence: 99%
“…19 (right panel) is the XLF of star-forming galaxies at z = 4, where the emission is mostly due to high-mass XRB, from the model by Volonteri et al (2017, see in particular their section 2.2 for assumptions and caveats). Briefly, they mapped the stellar-mass functions of Song et al (2016) into an XLF through the mainsequence of star-forming galaxies (Salmon et al 2015) and the SFR-LX scaling relation by Fragos et al (2013, model 269), which Lehmer et al (2016) demonstrated to be the best representation at z = 0 − 2.5. At logLX 42.5, the luminosity limit we applied to our luminosity functions, as the 42 logLX 42.5 regime was strongly affected by incompleteness, the density of star-forming galaxies is a factor Figure 19.…”
Section: The Agn Xlf At High Redshiftmentioning
confidence: 99%